A new approach to estimate the shear strength of curved corrugated steel webs. (April 2020) - Yossef, N.M.
Abstract: Innovative steel girders with corrugated webs have been recently developed utilizing advances in the fabrication and manufacturing technology. Additionally, horizontal curved web panels in curved steel girders have been incorporated into a variety of bridges and buildings. With several practical advantages and architectural-appearance requirements, the curved corrugated web panel is used. This paper presents a discussion of the buckling behaviour of horizontally curved corrugated webs under shear loading. An alternative approach to estimating the shear strength that combines local and global buckling for the curved corrugated web was presented. The presented formula includes elastic and inelastic domains for local and global buckling. The proposed approach is validated against experimental data. A thoroughly validated finite element model is used to provide additional assurance that the proposed equations are meaningful, and then additional factors affecting the behaviour of I-girders with curved corrugated webs are studied. The results show that the curvature parameter (Z) has a minor effect on the shear strength of the curved corrugated panel, whereas the corrugation angle and web thickness have a considerable effect on the behaviour of horizontally curved corrugated webs.